Forestry Economics Resources Sustainability Development in Indonesia (Study in Sunyalangu Village, Banyumas District, Central Java) - Murni, Hari Nur Cahya (Faculty of Economics and Business Universitas Jenderal Soedirman, 2025)
Joint Community Forest Resource Development Program (is a forest resource Development system that only exists in Java Island developed by Perum Perhutani. Forest Development must remain within the framework of sustainable development principles. In Banyumas Regency, the southern slopes of Mount Slamet are included in the protected area (Protected Forest and Conservation), both forests as economic, ecological and social functions. The purpose of this study was to analyze the factors that influence the sustainability of forest resources in the Joint Community Forest Resource Development program, through the economic sector and community participation in forest Development through the Joint Community Forest Resource Development program. The population of this study was the community of Sunyalangu Village, District, Banyumas Regency who worked as farmers cultivating Perum Perhutani land. The number of population members was approximately 150 people. This study shows that the Development program implemented in Banyumas Dsitrictdid not have a significant impact on the sustainability of forest resources. This study can be used as a reference on the sustainability of forest resources in the Development program seen from the perspective of the influence of individual characteristics of forest farmers on the participation of forest farmers in the implementation of the Development program which includes economic, social, environmental, and institutional dimensions. The importance of individual characteristics of forest farmers is the first concern in improving the Development of forest resource activities.